New Therapeutic Options for Type 2 Diabetes Mellitus and Their Impact Against Ischemic Heart Disease - Almutairi, Malak; Chan, Jordan S. F.; Ussher, John R. (Frontiers in Physiology, 2022)
Type 2 diabetes mellitus (T2DM) greatly increases risk for cardiovascular disease, including ischemic heart disease and myocardial infarction. With the completion of several cardiovascular outcomes trials (CVOTs) for new glucose-lowering therapies, including the sodium glucose cotransporter-2 (SGLT2) inhibitors and glucagon-like peptide-1 receptor (GLP-1R) agonists, we now have strong evidence alluding to the cardioprotective nature of these agents in people with T2DM. These agents have frequently been observed to reduce rates for 3-point major adverse cardiovascular events, which encompass death from cardiovascular causes, nonfatal myocardial infarction, or nonfatal stroke. Herein we will provide an overview on whether reductions in nonfatal myocardial infarction and ischemic heart disease status are a key component of the improved cardiovascular outcomes in people with T2DM treated with either SGLT2 inhibitors or GLP-1R agonists. Observations from preclinical studies will be compared to their clinical counterparts, while being further interrogated to define potential mechanisms that may account for SGLT2 inhibitor or GLP-1R agonist-induced cardioprotection against ischemic heart disease. A better understanding of the role these agents have in impacting the progression of ischemic heart disease in individuals with T2DM will have a substantial impact in our management of this patient population.